Volitional regulation of emotions produces distributed alterations in connectivity between visual, attention control, and default networks - Sripada, Chandra; Angstadt, Michael; Kessler, Daniel; Phan, K. Luan; Liberzon, Israel; Evans, Gary W.; Welsh, Robert C.; Kim, Pilyoung; Swain, James E. (NeuroImage (Orlando, Fla.), 2014)
The ability to volitionally regulate emotions is critical to health and well-being. While patterns of neural activation during emotion regulation have been well characterized, patterns of connectivity between regions remain less explored. It is increasingly recognized that the human brain is organized into large-scale intrinsic connectivity networks (ICNs) whose interrelationships are altered in characteristic ways during psychological tasks. In this fMRI study of 54 healthy individuals, we investigated alterations in connectivity within and between ICNs produced by the emotion regulation strategy of reappraisal. In order to gain a comprehensive picture of connectivity changes, we utilized connectomic psychophysiological interactions (PPI), a whole-brain generalization of standard single-seed PPI methods. In particular, we quantified PPI connectivity pair-wise across 837 ROIs placed throughout the cortex. We found that compared to maintaining one's emotional responses, engaging in reappraisal produced robust and distributed alterations in functional connections involving visual, dorsal attention, frontoparietal, and default networks. Visual network in particular increased connectivity with multiple ICNs including dorsal attention and default networks. We interpret these findings in terms of the role of these networks in mediating critical constituent processes in emotion regulation, including visual processing, stimulus salience, attention control, and interpretation and contextualization of stimuli. Our results add a new network perspective to our understanding of the neural underpinnings of emotion regulation, and highlight that connectomic methods can play a valuable role in comprehensively investigating modulation of connectivity across task conditions. •We examined effects of emotion regulation on intrinsic connectivity networks.•54 subjects, emotion regulation task with IAPS pictures, block design.•Connectomic PPI used to generate connectomes for Reappraise versus Maintain.•Reappraisal increases connectivity in visual, dorsal attention, default networks.